Land use changes due to energy policy as a determining factor for morphological processes in fluvial systems in São Paulo State, Brazil - Lupinacci, Cenira Maria [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; Heck Simon, Adriano Luis; Perez Filho, Archimedes (Wiley, 2017)
The number of hydroelectric dams used for energy production and the cultivation of sugar cane crops for ethanol production have increased significantly in the southeastern region of Brazil. These land use/land cover changes (LULCC) associated with energy policy can affect landscape changes over a range of temporal and spatial scales. This article focuses on how human–landscape interactions have influenced geomorphological dynamics in the lower course of the Piracicaba River for two different scenarios that represent pre-dam and post-dam conditions in 1962 and 2007, respectively, and the expansion of sugar cane crops after 1975. This assessment was performed by mapping land use and geomorphological changes in the study area in the 1962 and 2007 scenarios, in addition to quantifying the sedimentation rates upstream from the Barra Bonita Reservoir using 210Pb. The main land uses identified for the 1962 scenario were pastures, meadows, annual crops and forests. However, the main land use change was the expansion of sugar cane cropland from 4 to 39%. In the 1962 scenario, the lower course of the Piracicaba River had a predominantly meandering pattern, and there were pronounced alluvial plains in the region. In the 2007 scenario, oxbow lakes were not mapped, and the river terraces were reduced in area due to construction of the Barra Bonita Reservoir. The changes in the sedimentation rates indicate an association between the construction of the Barra Bonita Reservoir and the expansion of sugar cane crops. It was therefore not possible to assess the specific influences of each anthropogenic change on the sedimentation processes, reinforcing that the human–landscape systems in São Paulo State associated with energy policy are complex. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Brazil; energy policy; human–landscape systems; sedimentation rate